ANALISIS PENGELOLAAN DAN DISTRIBUSI BATANG KELAPA (STUDI KASUS PT.KELONA PELABUHAN PANTOLOAN) - Abdullah Abdullah; Anggun Majah; Elka Vina Detris Kola'a; Dilla Anastasya Aro; Nur Fatwa Laudiu (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This research determines the management and distribution strategy of coconut trunks at Pantoloan Harbor, Palu, with and with a focus on the challenges and strategies implemented by the entrepreneur, Pak Didi. This research uses a qualitative approach with in-depth interviews involving main stakeholders such as Mr. Didi and the logistics company Pt. Kelona. The research results show that logistics management is highly dependent on local networks and transportation systems, while the challenges faced include fluctuations in demand, weather, and increasingly fierce competition. These factors influence cost effectiveness and efficiency in the distribution process. This research contributes to understanding the challenges and best practices in managing the distribution of raw materials in the region.